Makna Simbolik Tradisi Kirab Pusaka sebagai Media Edukasi Budaya bagi Generasi Muda di Kabupaten Trenggalek - Ardelina, Putri Ayu Nur (STKIP PGRI Ponorogo Press, 2025)
The Kirab Pusaka tradition in Trenggalek Regency is an annual event rich in symbolism and local cultural values, yet it remains underexplored as an educational medium for younger generations. This study aims to reveal the symbolic meanings of heirloom objects and ceremonial elements, and to analyze the role of symbols in shaping cultural identity and youth character. A descriptive qualitative method was employed, using observation, interviews, and documentation for data collection. The findings indicate that symbols in the procession function not only as cultural artifacts but also as tools for internalizing noble values such as responsibility, togetherness, and pride in local identity. These symbols play a strategic role in sustaining cultural continuity and building character through tradition-based educational approaches.